Response to "Nutrition Education for Adolescents Using Animation Videos to Increase Knowledge, Attitudes and Breakfast Behavior" - Sugianto Hadi; Ngesti W. Utami; Tri Johan Agus Yuswanto (Aloha International Journal of Health Advancement (AIJHA), 2025)
Letter to editor: abstract is not required